Visualising Patterns in Women's Experiences of Intimate Partner Violence in the First 10 years of Motherhood. Issue 3 (February 2023) - FitzPatrick, Kelly M.; Brown, Stephanie; Hegarty, Kelsey; Mensah, Fiona; Gartland, Deirdre
Intimate partner violence (IPV) can involve patterns of physical, sexual and emotional abuse. Women typically experience physical IPV in combination with emotional IPV, while emotional IPV is often experienced in the absence of other types of IPV. There is very little known about women's experiences of these different types of IPV over time. The primary aim of this paper is to describe patterns in women's individual experiences of physical and/or emotional IPV across the first 10 years of motherhood. Data were drawn from a prospective pregnancy cohort of 1507 first-time mothers in Melbourne, Australia. Emotional, physical, and combined physical and emotional IPV were reported in the first, fourth and tenth year of motherhood using the Composite Abuse Scale. The overall prevalence of each type of IPV remained consistent across the three time-points, with emotional IPV alone being the most prevalent. There was substantial variability in women's experiences of IPV over time and there was no common progression from one type of IPV to another. Women were more likely to report IPV at more than one time-point if they experienced combined physical and emotional IPV, while for women who reported emotional or physical IPV alone this was more likely to be at a single time-point. A number of socio-demographic characteristics in early pregnancy were associated with a higher risk of reporting IPV at all three time-points, including being unemployed (RRR = 3.6; 95% CI: 2.1, 6.2) and being aged 18–24 years (RRR = 3.1; 95% CI: 1.8, 5.4). Knowledge of the variability and persistence of IPV in the first 10 years of motherhood, and factors associated with these experiences, can help tailor effective health and social service responses.